BAYESIAN APPROACH TO HIV-1 THROUGH MARSHALL - OLKIN DISCRETE UNIFORM DISTRIBUTION. - K., MARY GEORGE; C. B., PRASANTH; MEENAKSHI, G. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Human Immunodeficiency virus (HIV) has infected several million individuals in world wide. Various interventions have been implemented for early detection and prevention of transmission of HIV infection. This has progressively changed the clinical profile of HIV infected individuals. The advanced study about HIV-1 amounted to classify the stages of HIV patients into different categories according to the symptoms shown and the diseases appeared on one's body. By considering the distribution of CD4 +T count as a discrete distribution and adding stages of HIV patients as an additional parameter, Estimate posterior distribution for rate of CD4 +T count using Bayesian Approach. Here we calculate the CD4 + T count using discrete uniform distribution in any epoch of time. The time period follows an exponential distribution. The methodology used is Bayesian approach.